FOXO1 inhibits FSL-1 regulation of integrin β6 by blocking STAT3 binding to the integrin β6 gene promoter - Xu, Mingyan; Huang, Jie; Zhu, Feixiang; Shen, Kailun; Liu, Fan; Deng, Xiaoling (Frontiers in Cellular and Infection Microbiology, 2022)
Integrin β6 (ITGB6), an epithelial-specific receptor, is downregulated in the gingival epithelium of periodontitis and is associated with inflammation response and periodontitis development. However, the transcriptional regulatory mechanism of ITGB6 downregulation in the human gingival epithelium remains unclear. Fibroblast-stimulating lipopeptide-1 (FSL-1), an oral biofilm component, promotes an epithelial cell-driven proinflammatory response in periodontitis partially by suppressing ITGB6 expression. The aim of the current study was to investigate the transcriptional regulatory mechanism of ITGB6 inhibition by FSL-1 in human epithelial cells (HaCaT and primary human gingival epithelial cells), and to delineate the transcriptional mechanism of ITGB6 suppression in periodontitis. We found that FSL-1 inhibited ITGB6 transcription through increasing forkhead box protein O1 (FOXO1) expression and inhibiting signal transducer and activator of transcription 3 (STAT3) activation. Furthermore, FOXO1 bound to STAT3 directly, leading to decreased STAT3 phosphorylation induced by FSL-1. Consequently, the binding of phosphorylated STAT3 to the ITGB6 promoter was decreased, and ITGB6 transcription was therefore downregulated following FSL-1 stimulation. The reciprocal action of STAT3 and FOXO1 on ITGB6 downregulation was also confirmed by the immunostaining of the inflammatory epithelium associated with periodontitis. Our findings suggest that the interaction of FOXO1–STAT3 may be a useful signal target for the treatment of periodontitis.